The Analysis of Joint Inspection Repository System and The Proposed Solution - Misinem, .; Rika, Nuryani (INTI International University, 2023)
Technology advancements indicate that labor performed by humans is now more easily accomplished. Initially, this was carried out conventionally at the business where we studied report management and storage at PT. Kereta Api Indonesia Regional Division III. In this perspective, we suggested a solution based on the study that revealed the creation of a new system known as the Web-based Repository Joint Inspection System was judged required to facilitate staff members' handling, storing, and monitoring of current reports (for managers). The four (4) distinct user groups or access levels in this system are Administrator, User, Manager, and Safety. The Rational Unified Process, or RUP, was the development approach employed for this system. Still, this section goes into great detail about the uploading, downloading, and deleting of data. Following the upload, download, and removal of files, the system must be examined to make sure it is operational. Both feature testing and the black box method are used to test this system. It is possible to develop test scenarios based on how the system works.